Effect of Photodynamic Therapy using Different Protocols on Human Gingival Fibroblasts Cultured on Treated Root Fragments: An In Vitro Study: Effect of photodynamic therapy on gingival fibroblasts - Barzegar Reyhani, Negin; Aghayan, Shabnam; Hakimiha, Neda (Journal of Lasers in Medical Sciences, 2025)
Introduction: In periodontal therapy, the adhesion of fibroblasts and their attachment to cementum present a significant challenge. This study aims to evaluate the effects of photodynamic therapy (PDT) using various protocols on the adhesion and cell count of human gingival fibroblasts (HGFs) to root fragments using a scanning electron microscope (SEM). Methods: Root fragments were divided into four groups and subjected to different treatments: a control group receiving scaling and root planing (SRP), SRP combined with PDT using a 630 nm light-emitting diode (LED) and toluidine blue O (TBO), SRP combined with PDT using a 660 nm diode laser and methylene blue (MB), and SRP combined with PDT using an 810 nm laser and indocyanine green (ICG) as the photosensitizer (PS). Then, HGFs were cultured on the tooth fragments and evaluated using SEM after 72 hours of incubation. The adhesion of fibroblasts was assessed by counting the number of spindle-shaped fibroblasts, while their cell count was determined by counting the total number of cells. Adhesion was analyzed using the KruskalWallis test, and the cell count was analyzed using one-way ANOVA followed by Dunnett’s test. Results: PDT utilizing all three protocols significantly enhanced the adhesion of fibroblasts compared to the control group (P<0.05). However, there were no significant differences in adhesion between the PDT groups (P>0.05). Additionally, PDT with a 630 nm LED significantly promoted the cell count of fibroblasts compared to the control group (P=0.05). Conclusion: PDT utilizing three distinct protocols has been demonstrated to enhance the attachment of fibroblasts. Specifically, PDT employing a 630 nm LED has been found to significantly promote the cell count of fibroblasts under SEM.